2015
DOI: 10.1097/ta.0000000000000758
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic pulmonary pseudocysts after blunt chest trauma

Abstract: Prognostic/epidemiologic study, level IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
25
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 18 publications
4
25
0
Order By: Relevance
“…Pulmonary laceration is a tear of the lung parenchyma due to higher-energy blunt trauma than contusion and leads to a mechanical shear or puncture, disrupting the lung parenchyma. Because of the normal pulmonary elastic recoil, the tissues surrounding the cleavage plane pull back from it, resulting in round or oval space lesions on imaging, instead of the linear appearance typically seen in other solid organs [ 9 , 10 , 11 ]. Other names that have been used in the radiology literature include traumatic bullae, traumatic pneumatoceles, haematocele or traumatic lung cyst or pseudocysts [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Pulmonary laceration is a tear of the lung parenchyma due to higher-energy blunt trauma than contusion and leads to a mechanical shear or puncture, disrupting the lung parenchyma. Because of the normal pulmonary elastic recoil, the tissues surrounding the cleavage plane pull back from it, resulting in round or oval space lesions on imaging, instead of the linear appearance typically seen in other solid organs [ 9 , 10 , 11 ]. Other names that have been used in the radiology literature include traumatic bullae, traumatic pneumatoceles, haematocele or traumatic lung cyst or pseudocysts [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…In human literature TPPs occur most commonly in people < 30 years old, however, there are case reports of patients 30 years or older with pseudocyst formation following blunt thoracic trauma in circulation (2, 1921). Age predilection is assumed secondary to increased thoracic wall pliability in young adults leading to greater transmission of force through the chest leading to pseudocyst formation (2, 9, 22). The patient in this study is 1.5 years old and would be classified as a young adult.…”
Section: Discussionmentioning
confidence: 99%
“…The patient in this study is 1.5 years old and would be classified as a young adult. Vehicle trauma has been reported as the leading cause for TPP formation in many studies with those individuals being struck by a vehicle having a higher incident of TPP (9). The patient in this study falls within the latter group making the development of pseudocysts a plausible side effect of patients who are involved in motor vehicle accidents.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[3] The development of rare cardiac arrhythmias is an indirect indicator of the presence of cardiac involvement. [4,5] In addition to this, when an arrhythmia due to blunt chest trauma is detected, all types of arrhythmias, such as supraventricular tachycardia, atrial fibrillation, ventricular tachycardia and ventricular fibrillation, have been reported to develop from the atrium and ventricle of the heart. [6] after the injury.…”
Section: Introductionmentioning
confidence: 99%